On an inverse spectral problem for an integro-differential operator - Panakhov, Etibar S.; Sat, Murat (My University, 2012)
In this paper, we considered an inverse problem with two given spectrum for a boundary value problem with aftereffect and eigenvalue in the boundary condition and we showed that transformation operator was generalized degeneracy and we obtained a new proof of the Hochstadt's theorem concerning the structure of the difference q?(x)- q(x). © IDOSI Publications, 2012.
Keywords: Aftereffect; Eigenvalue; Spectrum